THE INFLUENCE OF ORGANIZATIONAL CLIMATE ON OCB AND EMPLOYEE ENGAGEMENT WITH JOB SATISFACTION AS AN INTERVENING VARIABLE - Wardono, Gadang; Moeins, Prof. Dr. Anoesyirwan; Sunaryo, Dr. Widodo (jfpublisher, 2022)
This research aims to determine the effect of organizational climate on OCB and employee engagement with job satisfaction as an intervening variable for permanent employees at middle management level of cement industry in Bogor. The research method uses mixed method with questionnaire for quantitative research and Delphi method for qualitative research. The research sample was 183 people from 334 permanent employees at middle management level. The conclusion in this research is there is a significant positive effect with the coefficient value Z1= 0.551 organizational climate on OCB. There is a significant positive effect with coefficient value Z2 = 0.578 organizational climate on employee engagement. There is a significant positive effect with the coefficient value xy = 0.939 organizational climate on job satisfaction. There is a significant positive effect with coefficient value yz₁ = 0.413 job satisfaction on OCB.